The fate of a neoproterozoic intracratonic marine basin: trace elements, toc and iron speciation geochemistry of The Bambuí Basin, Brazil - João Pedro Torrezani Martins Hippertt (2018)
Neoproterozoic marine systems are associated with major paleoecological changes that took place during the Ediacaran-Cambrian transition. During this timespan, the Bambuí basin located on east Brazil held a peculiar paleoenvironmental scenario. Due to its intracratonic evolution, the basin was partially disconnected from neighboring open marine systems. This isolated evolution rises a very interesting opportunity to understand how an isolated Neoproterozoic marine system evolved in contrast with regular open marine systems that ultimately evolved into the Cambrian Ecosystem. To understand the paleoenvironmental changes that took place in the Bambuí basin, we investigate the pre- glaciogenic deposits of Carrancas Formation and the post-glaciogenic mixed (Shale-Carbonate) successions of the Bambuí Group. Through the analysis of iron speciation, TOC, provenance, rare earthtrace elements data, and 13C and 18O analyses, our studies suggest a very complex environmental evolution. Firstly, our samples are marked by strong contamination of detrital continental material that can be related to an increased bioproductivity on both Carrancas Fm. and lower Bambuí group stratigraphic units, though provenance data show that all studied sediments probably share a common source rock, which likely changed the rare earth and trace elements contents of our samples. Iron speciation data, Ce anomalies and RSE enrichments shows that Lower Bambuí group stratigraphic units were likely deposited in an open marine scenario featuring high bioproductivity on shallow waters and euxinic incursions on predominant anoxic/ferruginous bottom waters. On the other hand, upper Bambuí stratigraphic units register a marine evolution in a restricted scenario, where anoxic ferruginous conditions probably reached surface waters. Finally, our data show that the lack of oceanic connection prevent the re-supply of marine sulfate, RSE, bionutrients such as Ba and ultimately of dissolved oxygen which may have decreased biological activity and probably damaged biological evolution, preventing the rise of a typical modern-like Cambrian ecosystem. In this sense, our data suggest that oceanic connectivity and proper re-supply of inorganic marine input were fundamental keystones in the development of complex life in the Ediacaran-Cambrian transition.